2020
DOI: 10.1101/2020.04.20.049437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial defenses against a natural antibiotic promote collateral resilience to clinical antibiotics

Abstract: As antibiotic-resistant infections become increasingly prevalent worldwide, understanding the factors that lead to antimicrobial treatment failure is essential to optimizing the use of existing drugs. Opportunistic human pathogens in particular typically exhibit high levels of intrinsic antibiotic resistance and tolerance 1 , leading to chronic infections that can be nearly impossible to eradicate 2 . We asked whether the recalcitrance of these organisms to antibiotic treatment could be driven in part by their… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…The availability of a functionally expressible design enabled physiological studies that would have been practically inaccessible otherwise. Because PYO and other phenazines permit P. aeruginosa to adopt metabolic strategies that lead to evasion of antibiotic treatments (10)(11)(12), it stands to reason that removal of these metabolites might offer an attractive therapeutic approach. Our results showing enhancement of synergistic killing by a designed PodA and tobramycin provide further motivation and the means to explore PodA's potential to be used as a biologic therapeutic for treating chronic P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of a functionally expressible design enabled physiological studies that would have been practically inaccessible otherwise. Because PYO and other phenazines permit P. aeruginosa to adopt metabolic strategies that lead to evasion of antibiotic treatments (10)(11)(12), it stands to reason that removal of these metabolites might offer an attractive therapeutic approach. Our results showing enhancement of synergistic killing by a designed PodA and tobramycin provide further motivation and the means to explore PodA's potential to be used as a biologic therapeutic for treating chronic P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…PYO confers a competitive advantage for P. aeruginosa by contributing to iron acquisition (6), anaerobic energy conservation (7), signaling (8), and biofilm development (9). It has also been shown that P. aeruginosa cells lacking the ability to synthesize phenazines (10), and PYO in particular (11), are more sensitive to conventional antibiotics when grown both planktonically and in the biofilm state; the mechanisms underpinning these phenomena are beginning to be elucidated (12). Accordingly, we reasoned that enzymatically degrading PYO within P. aeruginosa biofilms might improve conventional drug treatment, representing a strategy for biofilm control.…”
mentioning
confidence: 99%